2022
DOI: 10.1007/s10570-022-04689-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of phosphorylated chitosan/alumina nanoadditives for polymer performance improvement

Abstract: In this research, a new generation of ternary nanocomposites based on poly(ethylene terephthalate) (PET), phosphorylated chitosan and surface modified alumina nanoparticles were fabricated in four steps. The phosphorylation process was targeted for the insertion of phosphorus moieties as a flame retardant agent in the final PET nanocomposite. Likewise, environmentally friendly nano-alumina was used for PET matrix to improve the thermal properties of PET in collaboration with organic anchored phosphorus moietie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The findings concluded that antimicrobial activities were enhanced by grafting a phosphorus-containing monomer onto chitosan. Recently, Hatami et al, 87 has shown that the addition of 6 wt. % phosphorylated chitosan/nano-alumina in the poly (ethylene terephthalate) (PET) matrix resists the growth of bacteria ( E. coli ); however, the antibacterial effects were expected to be shown by nano-alumina and chitosan.
Figure 4.Factors affecting antibacterial activity.
…”
Section: Significance Of Phosphorylationmentioning
confidence: 99%
“…The findings concluded that antimicrobial activities were enhanced by grafting a phosphorus-containing monomer onto chitosan. Recently, Hatami et al, 87 has shown that the addition of 6 wt. % phosphorylated chitosan/nano-alumina in the poly (ethylene terephthalate) (PET) matrix resists the growth of bacteria ( E. coli ); however, the antibacterial effects were expected to be shown by nano-alumina and chitosan.
Figure 4.Factors affecting antibacterial activity.
…”
Section: Significance Of Phosphorylationmentioning
confidence: 99%
“…The active and homogeneous distribution of NPs is quite an impenetrable topic for scientists, which is importantly prejudiced by the intra-particle connections. Therefore, surface modifiers have been used to prevent this problem, placing them in a layer around the nanoparticle [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%